Pengaruh Diskon dan Kualitas Produk terhadap Keputusan Pembelian Produk Somethinc di Marketplace Shopee dengan Ulasan Produk Sebagai Variabel Moderasi - Muhibah Muhibah; Asep Ferry Bastian; Bagus Manunggal (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to analyze and determine the extent to which discounts and product quality influence purchasing decisions for Somethinc products, with product reviews as a moderating variable. The background of this study is based on the increasingly fierce competition in the cosmetics industry, which encourages manufacturers to implement effective marketing strategies, one of which is through providing discounts, improving product quality, and utilizing consumer reviews. The type of research used is quantitative with a causal approach. The data used is primary data obtained through the distribution of online questionnaires to respondents who meet the criteria. The study population is Somethinc product users who make purchases through the Shopee e-commerce platform. The sampling technique used the convenience sampling method with a sample size of 160 respondents. Data analysis was carried out using the Partial Least Square (PLS) method with the help of SmartPLS 3.0 software. The results of the study indicate that discounts have a positive and significant effect on purchasing decisions, indicating that the more attractive the discount offered, the more likely consumers are to make a purchase. Similarly, product quality has a positive and significant effect on purchasing decisions, meaning that the better the product quality perceived by consumers, the higher the tendency to buy. However, the results of the moderation effect test revealed that product reviews were unable to moderate the relationship between discounts and product quality on purchase decisions. This indicates that while product reviews can be a factor in consumer considerations, their influence is not strong enough to strengthen or weaken the relationship between these two independent variables and purchase decisions. This finding has implications for cosmetics businesses, particularly Somethinc, to focus more on pricing strategies and improving product quality as key factors in driving consumer purchase decisions.